The effects of syllable-awareness skills on the word-reading performances of students reading in a transparent orthography - Birkan Güldenoğlu (International Electronic Journal of Elementary Education, 2016)
The present study investigates the effects of syllable awareness on the word-reading process of students reading in a highly transparent orthography (Turkish). The participants were 90 second graders belonging to one of two distinct levels of syllable-awareness skills (50 with poor syllable-awareness skills and 40 with proficient syllable-awareness skills). The students were tested individually, using three computerized paradigms that assessed their syllable-awareness skills and their efficiency at determining the identicalness of real- and pseudo-word pairs. The obtained data were analysed using two different MANOVAs and one-way ANOVAs. Findings from the present study point out that syllable-awareness skills were one of the most important indicators of the word-reading performances of students reading in a transparent orthography. In the discussion section, evidence is discussed on the basis of how syllable-awareness skills have a positive effect on the word-decoding process for a highly transparent orthography, and some practical suggestions are given regarding how teachers can embed these skills in their reading curricula.